(untitled) (Bangladesh Journal of Agricultural Research, 2010)
An experiment was conducted to find out the efficacy of muriate of potash applied as a potash fertilizer and foliar spray with Bordeaux mixture + Cupraneb 224 kg/ha, Copper Hydroxide@ 2.24 kg/ha and Carbcndazim @ 750 g /ha to control red rust disease (Cephaleuros parasiticus) of tea. All treatments with fungicides and application of MP caused reduction in severity of red rust and gave increase in yield of made tea over the control, where any fungicide or MP was not applied. The tea yield was negatively and nearly correlated with severity of red rust disease. The most effective treatment was application of the potash fertilizer (MP), which was followed by foliar spray with Copper Hydroxide and Carbendazim. Keywords: Muriate of potash; foliar spray with fungicides; red rust disease. DOI: 10.3329/bjar.v35i2.5890 Bangladesh J. Agril. Res. 35(2) : 273-277, June 2010